To simplify the expression \((2 + 2i) / (1 - i)\), we can multiply the numerator and denominator by the conjugate of the denominator. The conjugate of \(1 - i\) is \(1 + i\).
Here's the step-by-step simplification:
- Multiply the numerator and the denominator by \(1 + i\):
\[ \frac{(2 + 2i)(1 + i)}{(1 - i)(1 + i)} \]
- Simplifying the denominator:
\[ (1 - i)(1 + i) = 1^2 - i^2 = 1 - (-1) = 1 + 1 = 2 \]
- Simultaneously, simplifying the numerator:
\[ (2 + 2i)(1 + i) = 2(1) + 2(i) + 2i(1) + 2i(i) = 2 + 2i + 2i + 2i^2 \] Since \(i^2 = -1\), we have:
\[ 2 + 2i + 2i - 2 = 0 + 4i = 4i \]
- Putting it all together, we have:
\[ \frac{4i}{2} = 2i \]
Now we can assess the statements provided:
- The simplified form is 2i. - True
- The simplified form is 4i. - False
- The simplified form is 2 + 2i. - False
- The simplified form is 4 + 4i. - False
- The simplified form is a complex number because complex numbers are closed under division. - True
- The simplified form is not a complex number because complex numbers are not closed under division. - False
So, the true statements are:
- The simplified form is 2i.
- The simplified form is a complex number because complex numbers are closed under division.